Pulse: Mining Customer Opinions from Free Text - Gamon, Michael; Aue, Anthony; Corston-Oliver, Simon; Ringger, Eric (Proceedings of IDA-05, the 6th International Symposium on Intelligent Data Analysis, 2005)
We present a prototype system, code-named Pulse, for mining topics and sentiment orientation jointly from free text customer feedback. We describe the application of the prototype system to a database of car reviews. Pulse enables the exploration of large quantities of customer free text. The user can examine customer opinion "at a glance" or explore the data at a finer level of detail. We describe a simple but effective technique for clustering sentences, the application of a bootstrapping approach to sentiment classification, and a novel user-interface.